Flavor Sensing in Utero and Emerging Discriminative Behaviors in the Human Fetus - Ustun, Beyza; Reissland, Nadja; Covey, Judith; Schaal, Benoist; Blissett, Jacqueline (Psychological Science, 2022)
The diet of pregnant women exposes fetuses to a variety of flavors consisting of compound sensations involving smell, taste, and chemesthesis. The effects of such prenatal flavor exposure on chemosensory development have so far been measured only postnatally in human infants. Here, we report the first direct evidence of human fetal responsiveness to flavors transferred via maternal consumption of a single-dose capsule by measuring frame-by-frame fetal facial movements. Pregnant women and their fetuses based in the northeast of England were involved in this study from 32 to 36 weeks’ gestation. Fetuses exposed to carrot flavor ( n = 35) showed “lip-corner puller” and “laughter-face gestalt” more frequently, whereas fetuses exposed to kale flavor ( n = 34) showed more “upper-lip raiser,” “lower-lip depressor,” “lip stretch,” “lip presser,” and “cry-face gestalt” in comparison with the carrot group and a control group not exposed to any flavors ( n = 30). The complexity of facial gestalts increased from 32 to 36 weeks in the kale condition, but not in the carrot condition. Findings of this study have important implications for understanding the earliest evidence for fetal abilities to sense and discriminate different flavors.